ANALISIS KINERJA KARYAWAN BERDASARKAN PERATURAN BUPATI NO. 115 TAHUN 2022 : (STUDI KASUS PADA BIDANG INDUSTRI KABUPATEN BLITAR) - Arrofi', Mohamad; Prasetyo, Whedy; Masrunik, Endah (Universitas Tulungagung, 2024)
The purpose of this research is to find out how the performance at the Blitar Regency Disperindag, especially in the Industrial Sector, is in accordance with Regent Regulation No. 115 of 2022 or not as expected. This research uses qualitative research methods with a case study approach which emphasizes understanding the problem and is based on specific real-world circumstances and also describes the data as it is and provides instructions on how to collect the shortcomings of the object of examination qualitatively, to analyse the data. Case study is one of several qualitative research methods used in this investigation. One of the data collection methods is the documentation, interview, and observation approach at the Blitar District Disperindag. The results showed that because the Blitar District Disperindag Office, especially the Industry Division, consistently responded that the Regent Regulation that had been made was used as a guideline in achieving performance, the research author concluded that employee performance was good. Regent Regulation No. 115 of 2022 provides guidelines for the performance of the Blitar Regency Disperindag in the Industry Sector to be able to comply with all existing regulations so that the performance carried out will be planned in accordance with what is expected.